Pharmacological effects of Artocarpus lakoocha methanol extract on inhibition of squalene synthase and other downstream enzymes of the cholesterol synthesis pathway - Shafaq; Tasleem Akhtar; Hafiz Muhammad Ishaq; Muhammad Shahzad (Taylor & Francis Group, 2022)
Context Artocarpus lakoocha Roxb. (Moraceae) is reported to possess antioxidant, anti-inflammatory, and anti-skin ageing agents.Objective This study evaluates the pharmacological effects of A. lakoocha leaves methanol extract on enzymes involved in the cholesterol synthesis pathway in high-fat diet-induced hyperlipidemic rats.Materials and methods Twenty-four male Wistar rats, weighing approximately 180-220 g, were divided into four groups: control, diseased (hyperlipidemic), A. lakoocha leaves extract treated, and simvastatin treated. The rats were fed with high-fat diet for 2 months to induce hyperlipidaemia, afterward, experimental groups received A. lakoocha leaves methanol extract (250 mg/kg) and simvastatin (10 mg/kg) orally until the 89th day of the experiment, while the diseased group continued to receive high-fat diet along with normal saline.Results It was found that A. lakoocha extract significantly lowered the serum total cholesterol, triglycerides, and low-density lipoprotein (LDL) levels, while effectively increasing serum high-density lipoprotein (HDL) levels as compared to the diseased group (p ≤ 0.05). The mRNA expression levels of squalene synthase and HMG-CoA reductase were found to be effectively down-regulated after the treatment with A. lakoocha leaves extract (17.45 ± 2.48 vs. 31.91 ± 5.292 and 5.85 ± 3.164 vs. 37.37 ± 6.492) and simvastatin (7.148 ± 0.76 vs. 31.91 ± 5.292, and 3.098 ± 2.09 vs. 37.37 ± 6.492) as compared to the diseased group.Discussion and Conclusions The results suggested that A. lakoocha leaves extract have observable beneficial effects on inhibition of enzymes involved in cholesterol synthesis pathway and improve lipid profile analogous to simvastatin.